De Synodo Diocesana - Benedict XIV (1792)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

De Synodo Diocesana - Benedict XIV (1792)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Ordenaçoens do Senhor Rey D. Affonso V - Rey D. Affonso V (Na Imprensa Da Universidade, 1792)
阿豐素五世的國王條例
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; History